2009
DOI: 10.3201/eid1512.090178
|View full text |Cite
|
Sign up to set email alerts
|

DelineatingAnaplasma phagocytophilumEcotypes in Coexisting, Discrete Enzootic Cycles

Abstract: Genetically distinct subpopulations have adapted to different niches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 34 publications
9
118
1
Order By: Relevance
“…However, sequence analysis revealed that the strains were most closely related to those recovered from large mammals across Europe suggesting that other, large mammal, hosts of I. ricinus present at the study site were responsible for these infections. Moreover, Bown et al (2009) observed that different A. phagocytophilum strains exist in discrete enzootic small mammal and large mammal cycles. The prevalence of infection of I. ricinus nymphs was low (1·12%) and the probability of a mouse feeding a nymph was also low (2·02%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sequence analysis revealed that the strains were most closely related to those recovered from large mammals across Europe suggesting that other, large mammal, hosts of I. ricinus present at the study site were responsible for these infections. Moreover, Bown et al (2009) observed that different A. phagocytophilum strains exist in discrete enzootic small mammal and large mammal cycles. The prevalence of infection of I. ricinus nymphs was low (1·12%) and the probability of a mouse feeding a nymph was also low (2·02%).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, rodents host both larvae and nymphs of I. ricinus (Milne, 1949;Gern et al 1998;Liz et al 2000;Karbowiak, 2004) and are competent transmission hosts of B. microti, A. phagocytophilum and B. burgdorferi s.l. B. microti is a small mammal specific pathogen whilst A. phagocytophilum infects both small mammals and large mammals such as deer, although it is thought that separate A. phagocytophilum strains exist in discrete small mammal and large mammal cycles (Bown et al 2009). Members of the B. burgdorferi s.l.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role of the white-tailed deer, Odocoileus virginianus, has been questioned (38,40) because it might harbor A. phagocytophilum strains not infectious for humans. In Europe, A. phagocytophilum has been detected in wildlife such as roe deer, red deer, and rodents (1,35,36,42,44), but their specific function in the transmission cycle of A. phagocytophilum is not completely understood (8).…”
mentioning
confidence: 99%
“…Most often the 16S rRNA gene was used, and a different pathogenic potential of distinct 16S rRNA gene variants of A. phagocytophilum has been suggested (40,60). However, 16S rRNA gene sequences were shown to not be informative enough to delineate distinct genotypes of A. phagocytophilum (8,9,12,71). Other genes that were used for typing include the groESL heat shock operon (64), the msp4 gene encoding one of the major surface proteins (17), and the ankA gene (39).…”
mentioning
confidence: 99%
“…50,51 We have focused on two of these strains, one of which is found in many wildlife hosts and humans (A. phagocytophilum-ha) and the other one of which is found in many wildlife hosts but not humans (A. phagocytophilum-v1). Future research should continue to investigate the origins and consequences of strain diversity in A. phagocytophilum, particularly because it affects variation in human risk of exposure to this emerging pathogen.…”
Section: Discussionmentioning
confidence: 99%